2021
DOI: 10.3389/fmats.2021.688594
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Piezoceramic-Based Sensing Technology Combined With Visual Domain Networks for Timber Damage Quantification

Abstract: Early detection of timber damage is essential for the safety of timber structures. In recent decades, wave-based approaches have shown great potential for structural damage assessment. Current damage assessment accuracy based on sensing signals in the time domain is highly affected by the varied boundary conditions and environmental factors in practical applications. In this research, a novel piezoceramic-based sensing technology combined with a visual domain network was developed to quantitatively evaluate ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Meng et al [52] investigated the repair of cracks on timber surfaces using piezoelectric ceramic active sensing. Xiong et al [53] combined the sensing technique based on piezoelectric ceramics with a visual domain network to quantitatively assess the damage condition of timber, and used deep neural network classification, which can effectively identify the crack condition of timber structures.…”
Section: Introductionmentioning
confidence: 99%
“…Meng et al [52] investigated the repair of cracks on timber surfaces using piezoelectric ceramic active sensing. Xiong et al [53] combined the sensing technique based on piezoelectric ceramics with a visual domain network to quantitatively assess the damage condition of timber, and used deep neural network classification, which can effectively identify the crack condition of timber structures.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [12] used a wave propagation monitoring technology system to explore the damage characteristics and evolution of wood specimens under axial compression and found that the amplitude of the signal can effectively reflect the damage law for wood. Xiong et al [13] proposed a new sensing technology based on piezoelectric ceramics combined with a visual domain network to quantitatively evaluate the damage to the wood. The experimental results showed that the method can be used to effectively and accurately identify the crack state for wooden structures.…”
Section: Introductionmentioning
confidence: 99%
“…During the past decades, structural health monitoring (SHM) has received rapidly increasing attention because it can help to protect structures from severe damage (Hou and Xia, 2021). An integral SHM system contains a lot of different kinds of sensors that should be installed on structures to record various types of responses (Yi et al, 2015(Yi et al, , 2017Xiong et al, 2021). Nowadays civil structures such as Guangzhou New TV Tower, Tsing Ma Bridge, and Hong Kong-Zhuhai-Macao Bridge are equipped with advanced SHM systems to ensure the serving structures are in healthy condition (Miguel et al, 2009;He et al, 2022).…”
Section: Introductionmentioning
confidence: 99%